2024
DOI: 10.3390/ijms25052929
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils at the Crossroads: Unraveling the Multifaceted Role in the Tumor Microenvironment

Deepika Awasthi,
Aditya Sarode

Abstract: Over the past decade, research has prominently established neutrophils as key contributors to the intricate landscape of tumor immune biology. As polymorphonuclear granulocytes within the innate immune system, neutrophils play a pivotal and abundant role, constituting approximately ∼70% of all peripheral leukocytes in humans and ∼10–20% in mice. This substantial presence positions them as the frontline defense against potential threats. Equipped with a diverse array of mechanisms, including reactive oxygen spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 194 publications
(228 reference statements)
0
2
0
Order By: Relevance
“…Studies by Qin F et al indicated that anti-TGF-b facilitates neutrophils recruitment and polarizes neutrophils towards an antitumor phenotype (N1) in CRC (39). Meanwhile, tumor infiltrating neutrophils can exert the role of antigen-presenting cells and heighten T cell proliferation (40). T FH cells are usually accompanied by high CXCR5, CD40, and CXCL13 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Qin F et al indicated that anti-TGF-b facilitates neutrophils recruitment and polarizes neutrophils towards an antitumor phenotype (N1) in CRC (39). Meanwhile, tumor infiltrating neutrophils can exert the role of antigen-presenting cells and heighten T cell proliferation (40). T FH cells are usually accompanied by high CXCR5, CD40, and CXCL13 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the ndings from GO, KEGG, and GSEA enrichment analyses, numerous differentially expressed genes (DEGs) showed enrichment in pathways related to the immune system.Neutrophil chemotaxis was associated with more DEGs during BP in all GOs. Previous studies have shown that neutrophils are a major component of TME [17], which can exert a tumour-killing effect by affecting T cells [18,19]. In this study, two groups with high and low levels of immune activation were also studied in depth, and noticeable variances were observed in the extent of immune cell in ltration between the two groups, and the level of immune cell in ltration in the high-immunity group was signi cantly higher than that in the low-immunity group, which may be associated with the high survival rate of the high-immunity group.…”
Section: Performance Of Risk Modelsmentioning
confidence: 99%